Influence of three-start spirally twisted tube combined with triple-channel twisted tape insert on heat transfer enhancement - Eiamsa-ard, S.; Promthaisong, P.; Thianpong, C.; Pimsarn, M.; Chuwattanakul, V. (My University, 2016)
In the present article, heat transfer enhancement by three-start spirally twisted tube combination with triple-channel twisted tape is studied numerically using RNG k-ε turbulence model. Influences of the tape width ratio (w/D = 0.1, 0.25, 0.34 and 0.5) and tube/tape arrangement (belly-to-belly and belly-to-neck arrangements) are described. The numerical results of a twisted tube without tape and a circular plain tube are also given for comparison. The results are reported in terms of velocity field, temperature field, turbulent kinetic energy, local Nusselt number distribution, average Nusselt number, pressure loss and thermal performance factor. It is found that heat transfer and friction factor increase with tape width ratio. At a given tape width, the systems in belly-to-neck arrangement are more efficient for heat transfer enhancement than the ones in belly-to-belly arrangement. The three-start spirally twisted tubes with twisted tapes in belly-to-neck arrangement at w/D = 0.1, 0.25 and 0.34 give higher Nusselt numbers than the twisted tube without tape up to 1.2%, 21% and 36%, respectively. The twisted tubes with triple-channel twisted tape in belly-to-belly arrangement provide higher Nusselt numbers than the twisted tube without tape up to 1.23%, 6.7%, 10% and 17%, respectively. The superior heat transfer of the combined devices in belly-to-neck arrangement (especially at large w/D) is attributed to the stronger interaction between the swirling flows induced by the tubes and those induced by the tapes. Moreover, the systems in belly-to-neck arrangement cause lower friction loss than the ones in belly-to-belly arrangement. Thus, the systems in belly-to-neck arrangement yield higher thermal performance factors. Among the studied cases, the twisted tube combined with triple-channel twisted tape in belly-to-neck arrangement at w/D = 0.34 possesses the maximum thermal performance of 1.32 at Reynolds number of 5000.
Keywords: Heat exchanger tube; Heat transfer; Three-start spirally twisted tube; Triple-channel twisted tape; Twisted tape